A Preference Ranking Method Based on Triangular Fuzzy Numbers for Green Supplier Selection (Journal of Informatics and Mathematical Sciences, 2020)
Green supplier selection is a process for establishing an effective supplier that fulfills environmental criteria in addition to economical criteria. However, the selection is not a straightforward process as it needs to consider multiple criteria with uncertain information. In order to overcome the uncertainty, we utilize a decision making method based on triangular fuzzy numbers in solving green supplier selection problems. Specifically, this paper aims to develop a preference of alternatives in the case of green supplier selection using fuzzy PROMETHEE method. Seven criteria, four alternatives and five decision makers were the main enterprises in this fuzzy decision making problem framework. Data was collected via personal communication with decision makers using five-point linguistic terms of triangular fuzzy numbers. The seven-step algorithm of fuzzy PROMETHEE with usual preference function and triangular fuzzy numbers was implemented to the case. The results of net flow values of alternatives indicate that supplier A1 is preferred over the other suppliers. More investigations about the fuzzy PROMETHEE method, particularly on the choice of preference functions and other applications are suggested in future research.
Keywords: Fuzzy number; Decision making; Green supplier selection; Preference function; PROMETHEE